BRAND IMAGE, CUSTOMER TRUST, AND CUSTOMER LOYALTY TOWARDS WILLINGNESS TO PAY OF SPORTS APPAREL DURING PANDEMIC COVID-19 IN INDONESIA - Hartanto, Michael; Rizky, M. Tubagus; Cahyaputra, Ivan; Tamara, Dewi (Directorate of Academic Research and Community Services, 2020)
As an effort to identify the underlying determinants of willingness to pay, this study seeks to examine brand image, customer trust, and customer loyalty that impacts directly on willingness to pay during the 2020 COVID-19 pandemic time frame. This study also seeks to identify the impact of customer trust and brand image towards willingness to pay though customer loyalty and to identify the indirect impact of customer trust and brand image towards willingness to pay during the 2020 COVID-19 pandemic time frame. Using a convenient sampling method, someone who ever bought some sports apparel during this COVID-19 pandemic were selected as the sample. Out of 230 distributed, 171 useful questionnaires were returned. Confirmatory factor analysis and path analysis were conducted using partial least square equation modelling. The results of this study showed that the willingness to pay of sports apparel during the pandemic covid 19 in Indonesia was influenced by the customer trust and customer loyalty but not significantly influenced by the brand image. This study has a different research originality by researching the relationship between brand image, customer trust, customer loyalty and willingness to pay of any sports apparel during a specific time frame of the 2020 COVID-19 Pandemic, also the impact of brand image and customer trust towards willingness to pay were a rare relation of a research.